Ecological Risk Assessment of Polycyclic Aromatic Hydrocarbons in Surface Sediments from the Upper Reach of Huaihe River. (19th October 2016) - Liu, Menglin; Feng, Jinglan; Kang, Bowen; Chen, Yunqi; Liu, Qun; Sun, Jianhui
Abstract : Based on the available toxicity data and the concentrations of polycyclic aromatic hydrocarbons (PAHs) in 16 surface sediments from upper reach of Huaihe River, overlapping areas of probability density curves and margin of safety (MOS10 ) were used to estimate the ecological risk of eight PAHs to aquatic organisms. The results indicated that the overlapping areas of Pyr, Nap, Fla, Ant, Phe, Ace, BaP, and Flu were 0.38, 0.29, 0.16, 0.11, 0.07, 0.03, 0.03, and 0.01, respectively. The risk of Pyr was the highest while that of Flu was the lowest. The overlapping area of ΣPAH8 was 0.72, higher than that of any individual PAHs due to their joint effect. The calculated MOS10 for Nap, Ace, Flu, Phe, Ant, Fla, Pyr, and BaP were 6.86, 5.42, 19.0, 2.72, 0.93, 0.75, 0.03, and 63.0, respectively. The probabilities of Nap, Ace, Flu, Phe, and BaP surpassing the 10th percentile value of the toxicity data were 0.07%, 0.30%, 0.05%, 1.97%, and 0.01%, respectively, suggesting minimal risk to aquatic organisms. However, the probabilities of Ant, Fla, and Pyr exceeding this value were 11.3%, 12.9%, and 64.8%, indicating potential risks. Among the individual PAHs, the ecological risk from Pyr was the highest, followed by Fla, Ant, Phe, Ace, Nap, Flu, and BaP. Additionally, the combined ecological risk of ΣPAH8 in the upper reach of Huaihe River was significantly higher than that of any individual PAH alone, which the probabilities of ∑PAH8 in excess of the 10th percentile of the toxicity data were 99.4%.